The use of illicit drugs as self-medication in the treatment of cluster headache: Results from an Italian online survey. (February 2016) - Di Lorenzo, C; Coppola, G; Di Lorenzo, G; Bracaglia, M; Rossi, P; Pierelli, F
Background: Cluster headache (CH) patients often receive unsatisfactory treatment and may explore illicit substances as alternatives. We aimed to explore this use of illicit drugs for CH treatment. Methods: We invited CH patients from an Internet-based self-help group to complete a questionnaire regarding their therapeutic use of illicit substances. Results: Of the 54 respondents, 29 were classified as chronic and 39 were drug-resistant cases. Fifty patients had previously tried subcutaneous sumatriptan, 40 had tried O2, and 48 had tried at least one prophylactic treatment. All 54 patients specified that they were dissatisfied with conventional treatments. Thirty-four patients had used cannabinoids, 13 cocaine, 8 heroin, 18 psilocybin, 12 lysergic acid amide (LSA), and 4 lysergic acid diethylamide (LSD). Discussion: Some patients with intractable CH decided to try illicit drugs concomitantly with cessation of medical care. Most of these patients found suggestions for illicit drug use on the Internet. Many patients seemed to underestimate the judicial consequences of, and had an overestimated confidence in the safety of, such illicit treatments. Physicians are often not informed by patients of their choice to use illicit drugs. This leads to questions regarding the true nature of the physician-patient relationship among dissatisfied CH patients.